Convective cloud vertical velocity and mass‐flux characteristics from radar wind profiler observations during GoAmazon2014/5. Issue 21 (15th November 2016) - Giangrande, Scott E.; Toto, Tami; Jensen, Michael P.; Bartholomew, Mary Jane; Feng, Zhe; Protat, Alain; Williams, Christopher R.; Schumacher, Courtney; Machado, Luiz
Abstract: A radar wind profiler data set collected during the 2 year Department of Energy Atmospheric Radiation Measurement Observations and Modeling of the Green Ocean Amazon (GoAmazon2014/5) campaign is used to estimate convective cloud vertical velocity, area fraction, and mass flux profiles. Vertical velocity observations are presented using cumulative frequency histograms and weighted mean profiles to provide insights in a manner suitable for global climate model scale comparisons (spatial domains from 20 km to 60 km). Convective profile sensitivity to changes in environmental conditions and seasonal regime controls is also considered. Aggregate and ensemble average vertical velocity, convective area fraction, and mass flux profiles, as well as magnitudes and relative profile behaviors, are found consistent with previous studies. Updrafts and downdrafts increase in magnitude with height to midlevels (6 to 10 km), with updraft area also increasing with height. Updraft mass flux profiles similarly increase with height, showing a peak in magnitude near 8 km. Downdrafts are observed to be most frequent below the freezing level, with downdraft area monotonically decreasing with height. Updraft and downdraft profile behaviors are further stratified according to environmental controls. These results indicate stronger vertical velocity profile behaviors under higher convective available potential energy and lower low‐level moisture conditions. Sharp contrasts in convective area fraction and mass flux profiles are most pronounced when retrievals are segregated according to Amazonian wet and dry season conditions. During this deployment, wet season regimes favored higher domain mass flux profiles, attributed to more frequent convection that offsets weaker average convective cell vertical velocities. Plain Language Summary: Radar observations collected during The Department of Energy's ARM Program Observations and Modeling of the Green Ocean Amazon (GoAmazon2014/5) campaign are used to measure thunderstorm air motions, area coverage and relative impact. Although there is no one‐size‐fits‐all solution for evaluating current Global Climate Model cloud simulation capabilities, new observations including those found in this study may provide the necessary information to improve climate models to the scales they attempt to represent. Our findings on the vertical structure of Amazon convective clouds, and the sensitivity of cloud intensity to the changes in the atmospheric conditions that trigger those clouds, complement previous thunderstorm observations. Contrasts in the observed cloud properties are most pronounced when separated according to Amazonian "wet" and "dry" season conditions. For example, while deeper clouds were more frequent during the wet season, the more intense vertical air motions were observed within dry season storms. Key Points: Characterization of vertical velocity, area fraction, and mass flux profiles for Amazon convection Profiles aligned to be statistically representative of ensemble and aggregate convective properties to GCM domain scales Convective profiles indicate significant sensitivity to environmental forcing, wet and dry season regime controls